2022
DOI: 10.3389/fcvm.2022.1000812
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the individual roles of FII, FV, and FX activity in the thrombin generation process

Abstract: Thrombin generation (TG) is known as a physiological approach to assess the hemostatic function. Although it correlates well with thrombosis and bleeding, in the current setup it is not sensitive to the effects of fluctuations in single coagulation factors. We optimized the calibrated automated thrombinography (CAT) method to quantify FII, FV and FX activity within the coagulation system. The CAT assay was fine-tuned for the assessment of FII, FV and FX by diluting the samples in FII-, FV-, or FX-deficient pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…Administration of andexanet after trauma shortened lag time to a similar extent in all animals, while the peak height exhibited a dose-dependent restoration immediately after andexanet application. This finding aligns with a previous research, 28 which demonstrated a linear correlation between FXa concentration and peak height. The most prolonged restoration of thrombin generation was observed in animals that received a 500-mg bolus of andexanet followed by a 2-hour infusion.…”
Section: Discussionsupporting
confidence: 93%
“…Administration of andexanet after trauma shortened lag time to a similar extent in all animals, while the peak height exhibited a dose-dependent restoration immediately after andexanet application. This finding aligns with a previous research, 28 which demonstrated a linear correlation between FXa concentration and peak height. The most prolonged restoration of thrombin generation was observed in animals that received a 500-mg bolus of andexanet followed by a 2-hour infusion.…”
Section: Discussionsupporting
confidence: 93%